The Effect of Work Stress and Competence on Employee Performance with Work Motivation as A Variable Moderation of PT PLN (Persero) Unit Employees Medan Customer Service Officer - Fara Dika Sandi; Kiki Farida Ferine; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2025)
This study aims to analyze the influence of job stress, competence, and work motivation on employee performance, and to examine the role of moderating effects in this relationship. This study uses a quantitative approach with the Partial Least Square (PLS) analysis method on data obtained from employee respondents. The results show that competence and work motivation have a positive and significant effect on employee performance. Competence has the most dominant influence with a coefficient of 0.608 and a p-value of 0.000, followed by work motivation with a coefficient of 0.315 and a p-value of 0.000. Conversely, job stress does not have a significant effect on employee performance, as indicated by a p-value of 0.263. In testing the moderating effects, only one moderation has a significant effect on performance (p = 0.028), although in a negative direction, while another moderating effect is rejected because it is not statistically significant (p = 0.105). These findings emphasize the importance of improving competence and work motivation in driving performance, as well as the need for organizational management to identify and manage factors that have the potential to weaken the relationship between variables. This research provides practical contributions to organizations in designing more effective human resource development strategies.